2006
DOI: 10.1002/path.1918
|View full text |Cite
|
Sign up to set email alerts
|

The absence of CCL2 expression in cervical carcinoma is associated with increased survival and loss of heterozygosity at 17q11.2

Abstract: To determine whether CCL2 mRNA expression is beneficial or detrimental for cervical cancer patients, the association between the expression of this molecule by cervical tumour cells, the number of tumour‐associated macrophages, and clinicopathological parameters such as recurrence, relapse‐free survival, and overall patient survival was investigated. In cervical cancer samples from 93 untreated cervical cancer patients, the CCL2 mRNA expression level was quantified using RNA in situ hybridization and verified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 47 publications
(69 reference statements)
3
46
0
Order By: Relevance
“…11,14 We have shown that expression of CCL2 (MCP-1) by the cervical cancer cells is associated with an increased number of macrophages and a decreased disease-free survival of cervical carcinoma patients. 15 Furthermore, we have observed a down-regulation of the expression level of proinflammatory cytokines such as GM-CSF, TNF-a, and IL-12 in cervical carcinoma cell lines. 12 GM-CSF, TNF-a, and IL-12 are important in profiling immune reactivity.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…11,14 We have shown that expression of CCL2 (MCP-1) by the cervical cancer cells is associated with an increased number of macrophages and a decreased disease-free survival of cervical carcinoma patients. 15 Furthermore, we have observed a down-regulation of the expression level of proinflammatory cytokines such as GM-CSF, TNF-a, and IL-12 in cervical carcinoma cell lines. 12 GM-CSF, TNF-a, and IL-12 are important in profiling immune reactivity.…”
mentioning
confidence: 87%
“…28 We have previously shown that CCL2 expressed by cervical tumor cells is associated with the presence of TAM at the tumor site. 15 In addition to CCL2, TNF-a expression is often correlated with large numbers of inflammatory cells. 8,29 Indeed, a positive association between TNF-a expression and stromal TAM was found.…”
Section: Discussionmentioning
confidence: 99%
“…However, these chemokines are usually associated with pro-rather than anti-tumor activities. For example, CCL2 (MCP-1), which is overexpressed in a wide range of cancers [234], is associated with poor prognosis in breast, colorectal, cervical and thyroid cancers [235][236][237][238][239]. Tumor-derived CCL2 plays a pro-tumor role by recruiting inflammatory monocytes to pulmonary metastases [240] and MDSCs to the tumor microenvironment [241], as well as promoting angiogenesis [242], tumor cell proliferation [243] and migration [244].…”
Section: Neutrophil Activation In Cancermentioning
confidence: 99%
“…Probes were prepared and cervical carcinoma sections were stained for versican mRNA as previously described. 28 In short, 3 mm paraffin sections were pre-treated and hybridized with 100 ng/ml digoxigenin-labeled mRNA probe diluted in hybridization mixture containing 0.3 M NaCl and 0.03 M saline sodium citrate (SSC). Hybridization was allowed for 16 h at 55 1C in a humidified chamber.…”
Section: Mrna In Situ Hybridizationmentioning
confidence: 99%